Pengaruh Perilaku Konsumen Dalam Membeli Sayur Hidroponik Non Pestisida Di Kota Padang - Leovita, Angelia; Rangkuti, Irfan; Dermawan, Alvindo (Musamus University, 2022)
The agricultural sector is one of the sectors contributing to income in Indonesia's development. The agricultural sector, which supports human needs, also contributes to negative impacts in environmental damage, including the green revolution. The purpose of this study was to analyze the influence of consumer behavior in purchasing decisions on hydroponic non-pesticide vegetables in the city of Padang. The method used sampling techniques, namely non-probability sampling withmethod incidental sampling, samples taken as many as 40 respondents. The results in the study were based on linear regression analysis that cultural factors, social factors did not have a significant effect on purchasing decisions for hydroponic non-pesticide vegetables in the city of Padang